2021
DOI: 10.1302/2633-1462.27.bjo-2021-0064.r1
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcomes in acute and chronic periprosthetic hip and knee joint infection with a multidisciplinary approach

Abstract: Aims Periprosthetic hip and knee infection remains one of the most severe complications following arthroplasty, with an incidence between 0.5% to 1%. This study compares the outcomes of revision surgery for periprosthetic joint infection (PJI) following hip and knee arthroplasty prior to and after implementation of a specialist PJI multidisciplinary team (MDT). Methods Data was retrospectively analyzed from a single centre. In all, 29 consecutive joints prior to the implementation of an infection MDT in Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…While surgical strategies have evolved and recent shifts in practice are already aligned with many of these guidelines, 30,31 psychological support is increasingly seen to be crucial for PJI patients and may stand out as the most challenging to address. Evidence from the INFORM programme described the psychological impact on patients and their unmet needs, 4,21,22,32 but more recent studies have also identified this gap in provision and the need for more research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…While surgical strategies have evolved and recent shifts in practice are already aligned with many of these guidelines, 30,31 psychological support is increasingly seen to be crucial for PJI patients and may stand out as the most challenging to address. Evidence from the INFORM programme described the psychological impact on patients and their unmet needs, 4,21,22,32 but more recent studies have also identified this gap in provision and the need for more research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeon expertise is also an important factor in the management of infections after hip HA. A multidisci-plinary approach has proven to be beneficial in decreasing hospital stay, reducing the need for multiple revision surgical procedures, decreasing the number of different antibiotics needed, and decreasing failure rates 19,20,78 . As such, surgical intervention should be performed by a surgeon with good fundamental knowledge of both the diagnosis and treatment of PJI.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Treatment for PJI after hip HA should be centralized at specialty centers with well-established multidisciplinary teams to minimize treatment failure 20,78 . B *According to Wright 114 , grade A indicates good evidence (Level-I studies with consistent findings) for or against recommending intervention; grade B, fair evidence (Level-II or III studies with consistent findings) for or against recommending intervention; grade C, poor-quality evidence (Level-IV or V studies with consistent findings) for or against recommending intervention; and grade I, insufficient or conflicting evidence not allowing a recommendation for or against intervention.…”
mentioning
confidence: 99%
“…Die optimale Strategie zur Antibiotikatherapie bei der zweizeitigen PPI-Sanierung wird diskutiert [ 24 ]. Izakovicova et al.…”
Section: Diskussionunclassified